The Microbiological Quality of Harvested Rainwater System for Domestic Use in Gambang, Malaysia - Qasim, Ban; Abdul Syukor, Abd Razak; Siddique, Md. Nurul Islam (2017)
The use of roof-collected rainwater as a freely available and sustainable alternative to be used as drinking water that is produced by many drinking water companies around the world is increasing significantly. Malaysia is blessed with an ample supply of water and abundant rains. However, increasing usage by the industry, agriculture and by household users is straining the existing water supply infrastructure. The costs of adding to this infrastructure and that of replacing the ageing system are further burdening Malaysia’s exchequer. At the present, Malaysia depend upon rainwater that falls over hills and countryside, which is collected then into large servitors inside ground as groundwater. Initially, rainwater is free of microbial contamination, but it may become contaminated by animals, surrounding environment that can help pathogens to grow in stored rainwater system and may result in a significant human health risk from infectious diseases. In this study rainwater samples were collected from rainwater Harvesting system tank that is located in a rural area in Gambang at University of Malaysia Pahang. The target microorganism were E. coli and total coliform which were measured by using colilert quanti tray 2000 at the University Environmental Lab. The experiments were performed for 6 months’ period time with different time intervals or which is known as southeast monsoon in Malaysia to evaluate the seasonal change on the microbial parameters variation and their presence in harvested rainwater tank.